Readiness analysis of electronic medical record implementation in inpatient services using the DOQ-IT Method at Pusri Hospital Palembang - Budiantono, Budiantono; Widiyanto, Wahyu Wijaya (Institute of Computer Science (IOCS), 2025)
This study explored how ready Pusri Hospital Palembang was to implement electronic medical records in its inpatient services, using the Doctor’s Office Quality – Information Technology (DOQ-IT) framework. Using a quantitative, cross-sectional approach, data were gathered from 43 health workers and administrative staff through validated questionnaires. The assessment focused on four key areas: readiness of human resources, organizational work culture, governance and leadership, and the hospital’s technology infrastructure. Results showed that while infrastructure and governance were relatively ready, the readiness of staff and the work culture still needed improvement. Statistical analysis confirmed that all four factors significantly influenced the hospital’s overall readiness to adopt electronic medical records. Although the hospital demonstrated moderate readiness, the findings highlight the need for enhanced training and better infrastructure planning to ensure a smoother digital transition. This study offers practical insights for hospital leaders and health policymakers aiming to advance digital transformation in healthcare settings.